Can a Telephone Encounter Replace in Person Follow-up after IUD Insertion? [14G]. (May 2018) - Chen, Stephanie; MacIsaac, Laura; Belkin, Jori; Overbey, Jessica; Pan, Stephanie
Abstract : INTRODUCTION: Limited research informs the recommendation for a 4 - 6 week follow-up surveillance visit after IUD insertion. We explored whether surveillance could occur over the phone instead of in-person without affecting continuation rates or adverse events. METHODS: Subjects were offered in-person or telephone follow-up 4 - 6 weeks after IUD insertion. All subjects were called at 6 months to assess if and why they had discontinued IUD use, or if they had any adverse events including expulsion, pregnancy, or pelvic infection. Subjects were also asked about string check attempts and success and their preferred method for IUD surveillance. Group demographics and outcome measures were compared using Chi-square, Fisher's exact, T-test and Wilcoxon tests as appropriate. RESULTS: 47 and 131 patients enrolled respectively in the in-person and telephone follow-up groups. Demographics and medical history were not significantly different between the groups. The majority of subjects were white, college educated, privately insured, and nulliparous. Of all subjects who completed the 6-month assessment, 138 (94%) reported still having their IUD in place, 8 had discontinued, and 1 had an expulsion. Subjects in the two groups had similar IUD continuation rates at 6 months (p=0.70). Unscheduled visits and ability to feel strings were similar between the groups. CONCLUSION: We observed similar 6-month continuation rates, no evidence of increased unscheduled visits, expulsions or adverse events in the telephone group compared to the in-person group. More subjects chose phone follow-up. The 4 - 6 week telephone follow-up was comparable to in-person IUD follow-up in our population.